A new way to net-shaped synthesis tungsten steel by selective laser melting and hot isostatic pressing. (September 2020) - Kang, N.; Lu, J.L.; Li, Q.G.; Cao, Y.N.; Lin, X.; Wang, L.L.; Huang, W.D.; El Mansori, M.
Abstract: In this work, a novel tungsten steel was in-situ prepared using selective laser melting (SLM) and hot isotropic pressing (HIPing). The sample is firstly prepared by SLM from powder mixture of maraging steel and WC for the net-shaped manufacturing requirement. Then, the effects of HIPing on microstructure evolution and mechanical properties of SLMed WC/maraging steel composite were investigated with focus on in-situ reaction. The as-SLMed sample presents a composite structure of γ (Fe, Ni) (austenite) and WC, which transits into α-Fe (ferrite and martensite) matrix with a large amount of Fe(Ni)–W–C η phase precipitates after HIPing. The η phase, which shows two morphologies (sub-micro and nano scales), locates mainly in grain boundary and inner-grain of α-Fe, respectively. The interfaces between η, WC and α-Fe were determined using transition electron microscopy from barely existing partial melted WC. A stable graded multi-scaled structure appears between partial melted WC and matrix. After the HIPing process, the ultimate tensile strength and yield strength increase from 980 MPa to 561 MPa–1470 MPa and 1025 MPa, respectively, with a slight decrement in elongation from 7% to 6%. Highlights: Defect-free tungsten steel was prepared by SLM and HIPing. The processed sample presents equilibrium bcc α-Fe grains with η precipitate. Micro/nano-η (Fe (Ni)–W–C) locates in grain boundary and inner-grain of α-Fe. This novel tungsten steel possesses high tensile and yield strength.